Embodied Instruction: An Exploration and Qualitative Comparison of Expression and Performance of Yoga Instruction - Reeves, Tegan; White, Crystal L. (Frontiers in Education, 2021)
Background: An inclusive, whole-child model of education is shifting the paradigm into an integrative mind-body approach. Toward contextualizing learning at the close of the cartesian era, the current work explores embodied instruction through the lens of a teacher whose primary focus is the integration of mind and body. Perhaps the longest standing curriculum aimed at embodied learning, yoga provides a unique perspective on techniques and experiences of embodied teaching. Method: This case study employed an in-depth explorative participatory design to observe instructor intentions in and performance of instruction. Consecutive interviews (5) in conjunction with participatory observation of weekly classes (8) were audio recorded, transcribed verbatim, and triangulated with researcher memos. A grounded and comparative methodology was used to analyze expressed understanding of embodied learning and performed instruction. Results: In-depth interviews revealed four themes of expressed understanding of embodied instruction: energetic state, personality of instruction, inviting experience and student vulnerability. Participatory observations revealed four themes of performance of embodied instruction: scoping, cadence, silence, and inviting practice. Overlap in expressed understanding and observed instruction were found in each theme. An example of the expressed understanding of a thematic concept is inviting experience: “If someone comes in the very first time and the teacher is very invasive and says, “Do this, do this, do this.” And the next pose the teacher is hovering over them, you are not going to go back. You are going to hate it so much [I] let people be really all over the place at the beginning as long as they are safe. [I] allow them that kind of freedom, initially”. This was further supported in the observed instruction; an example of this is: “We’re going to play with [a posture]. that firmness in your abs, engage the core so a foot might lift. Maybe both feet.” And “with the arms firm, maybe the legs straighten”. Conclusion: The current study yields preliminary insight into yoga instruction strategies to support further development of embodied teaching and learning.